2021
DOI: 10.3390/vaccines9080854
|View full text |Cite
|
Sign up to set email alerts
|

Romanian Medical Students’ Attitude towards and Perceived Knowledge on COVID-19 Vaccination

Abstract: In Romania, the first phase of the COVID-19 vaccination campaign prioritized medical personnel, which included healthcare students. This study aimed to assess their knowledge, attitudes towards, and perception of COVID-19 vaccination. An anonymous, single-answer, 42-item online survey was conducted from 12 January until 3 March 2021, in the country’s largest University of Medicine and Pharmacy. Among the 1581 respondents (14.9% response rate), 88.5% were pro-vaccination, 7.8% were undecided, and 3.7% were vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
42
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 11 publications
5
42
1
Order By: Relevance
“…The findings regarding the perceived harm of a COVID-19 vaccine indicate that those with lower perceived vaccine risk had a higher likelihood of intention to use the COVID-19 vaccine. Similar results were reported by a majority of studies conducted among health science students [22,24,25,27,[34][35][36][37][38][39][40][41]. These findings suggest that concerns of serious or long-term adverse effects of a novel vaccine were important factors influencing decisions to not get vaccinated [25,27,34,36].…”
Section: Discussionsupporting
confidence: 86%
“…The findings regarding the perceived harm of a COVID-19 vaccine indicate that those with lower perceived vaccine risk had a higher likelihood of intention to use the COVID-19 vaccine. Similar results were reported by a majority of studies conducted among health science students [22,24,25,27,[34][35][36][37][38][39][40][41]. These findings suggest that concerns of serious or long-term adverse effects of a novel vaccine were important factors influencing decisions to not get vaccinated [25,27,34,36].…”
Section: Discussionsupporting
confidence: 86%
“…Anderson E. [ 27 ] pointed out that poorly trained medical staff can be a barrier to immunizing children. Furthermore, we identified recent, worrying data regarding Romanian medical students: only 90.7% of them would recommend giving an additional vaccine to a child or adult, and only 32.6% had received, for example, the influenza vaccine in the 2020/21 season [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous international meta-analysis of the proportion of vaccine hesitancy among the general population suggested that 20% of the participants intended to refuse COVID-19 vaccination [20]. Regarding medical students, the rate of vaccine hesitancy reported in previous studies has varied considerably due to the different definitions of the concept or timing of investigation in each study [9,10,[21][22][23]. The availability of vaccination, or the percentage of vaccinated students might be associated with vaccination hesitancy.…”
Section: Discussionmentioning
confidence: 99%